Are Internet users in Slovenia willing to pay for fast broadband and what drives them to migrate?. Issue 1 (1st January 2019) - Švigelj, Matej; Hrovatin, Nevenka; Zorić, Jelena
Abstract: The European Union (EU) member states are faced with a significant gap between availability of high-speed broadband and the share of households subscribed to such Internet access. This paper investigates the determinants of Internet users' willingness to pay (WTP) for next-generation access (NGA) in Slovenia. Following the EU Digital Agenda target whereby all households should have Internet access of at least 30 Mbps by 2020, the WTP for an Internet speed of 30 Mbps is analysed. The results show that characteristics relating to the current use of Internet services and characteristics of Internet users both play an important role in explaining the WTP for NGA In particular, the presence of a student or pupil in the household, household income, subscription to mobile broadband and the quality of Internet services positively influence the WTP decision, while respondents that are employed or are already subscribed to fibre have lower WTP The results of our analysis may help Internet service providers and policymakers identify remedies which can reduce the demand gap for NGA networks.